If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (u + -1)(u + 8) = x Reorder the terms: (-1 + u)(u + 8) = x Reorder the terms: (-1 + u)(8 + u) = x Multiply (-1 + u) * (8 + u) (-1(8 + u) + u(8 + u)) = x ((8 * -1 + u * -1) + u(8 + u)) = x ((-8 + -1u) + u(8 + u)) = x (-8 + -1u + (8 * u + u * u)) = x (-8 + -1u + (8u + u2)) = x Combine like terms: -1u + 8u = 7u (-8 + 7u + u2) = x Solving -8 + 7u + u2 = x Solving for variable 'u'. Combine like terms: x + -1x = 0 -8 + 7u + u2 + -1x = 0 The solution to this equation could not be determined.
| 9.75=100+8.25*1 | | 125000-62500=0.25y | | sqrt(x+23)+sqrt(2-x)=sqrt(-2x-1) | | 18/5a=3/5 | | 16/11*-18/36 | | y=100+8.25x | | -7/8-1/2= | | 10x-36=180 | | 6/7=3z/42 | | 5(2x+1)-7(x-2)=-1 | | x+(x+1)+(x*2)=29 | | x^3+0.6x^2-13.4x+3.9=0 | | 2x+21-6x=5 | | 25xy^2/15y | | 3n^2=14+n | | -6(x-6)+7=43 | | x^2/3=49 | | 7/9y-28=70 | | 6v+5(5+4v)=155 | | 4x^3+28x^2+48x=0 | | -36/(-4)= | | 2w^2-10w+12=0 | | -9(-2+6n)=504 | | 2-8a=-5 | | 5/3 | | 2x+45=65 | | (5/6)/3 | | x=x^3-3x^2+5 | | 111=-3(8x+3) | | 3x-14x=0 | | 5/6/3= | | 2(7+4n)=-10 |